Engaging College Communities in Collaborative Strategic Planning - Dawn Shinew; Brian Campbell; Tracy Huziak-Clark; Christina Lunceford; Trinka Messenheimer; Mary Murray; Patrick Pauken; Ray Schneider; Mark Seals; Maureen Wilson; Deborah Wooldridge (Academic Chairpersons Conference Proceedings, 2020)
Strategic planning is often met with skepticism. Too often, this process goes nowhere and changes nothing. The leadership team from Bowling Green State University’s College of Education and Human Development share a collaborative strategic process focused on building a common college identity, concrete actions, and a collective sense of accountability.
Keywords: strategic plan; collaboration; team-building; engagement; accountability